Climate actions, market beliefs, and monetary policy - Barbara Annicciarico; Fabio Di Dio; Francesca Dilusio (European Commission, 2022)
This paper studies the role of expectations and monetary policy on the economy's response to climate actions. We show that in a stochastic environment and without the standard assumption of perfect rationality of agents, there is more uncertainty regarding the path and the economic impact of a climate policy, with a potential threat to the ability of central banks to maintain price stability. Market beliefs and behavioral agents increase the trade-offs inherent to the chosen mitigation tool, with a carbon tax entailing more emissions uncertainty than in a rational expectations model and a cap-and-trade scheme implying a more pronounced pressure on allowances prices and inflation. The impact on price stability is worsened by delays in the implementation of stringent climate policies, by the lack of confidence in the ability of central banks to keep inflation under control, and by the adoption of monetary rules tied to expectations rather than current macroeconomic conditions. Central banks can implement successful stabilization policies that reduce the uncertainty surrounding the impact of climate actions and support the greening process while staying within their mandate.
Keywords: D83; Q50; E32; E71; 330; Monetary policy; climate policy; expectations; inflation; market sentiments; business cycle